2011
DOI: 10.3389/fnins.2011.00018
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuronal Ras Activity in Adult Hippocampal Neurogenesis and Cognition

Abstract: Hippocampal neurogenesis in the adult mammalian brain is modulated by various signals like growth factors, hormones, neuropeptides, and neurotransmitters. All of these factors can (but not necessarily do) converge on the activation of the G protein Ras. We used a transgenic mouse model (synRas mice) expressing constitutively activated G12V-Harvey Ras selectively in differentiated neurons to investigate the possible effects onto neurogenesis. H-Ras activation in neurons attenuates hippocampal precursor cell gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Small GTPases from the Ras family are highly evolutionary conserved, molecular switches involved in important cellular responses such as proliferation, differentiation, and survival ( 28 ). We previously showed that hyperoxia reduces Ras activity and that transgenic mice overexpressing Ras under the synapsin 1 promoter ( syn Ras) to drive the selective overexpression of V12-Ha-Ras in post-mitotic neurons ( 29 ) are protected against hyperoxia-induced cellular degeneration ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small GTPases from the Ras family are highly evolutionary conserved, molecular switches involved in important cellular responses such as proliferation, differentiation, and survival ( 28 ). We previously showed that hyperoxia reduces Ras activity and that transgenic mice overexpressing Ras under the synapsin 1 promoter ( syn Ras) to drive the selective overexpression of V12-Ha-Ras in post-mitotic neurons ( 29 ) are protected against hyperoxia-induced cellular degeneration ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, our previous work demonstrated the importance of the mitogen-activated protein kinase (MAPK) signaling pathway ( 22 , 27 ). It was shown that hyperoxia reduces Ras GTPase activity and downstream signaling pathways (e.g., phosphorylation of the extracellular regulated kinase (ERK)) ( 27 ), which modulate important cellular responses such as differentiation and survival ( 28 ). Of note, using syn Ras-transgenic mice overexpressing constitutively activated Ras ( 29 ) in the neuronal compartment, we confirmed the important involvement of this pathway demonstrating protection against oxygen-induced cell death ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggest that ACE inhibitors may have a protective effect on cognition (Gard, 2008). However, the effects of either ACE inhibitors or ARBs on cognition have been controversial (Manns et al, 2011). Recent evidence suggests that the renin angiotension system plays a central role in linking hypertension to cognitive function (Hajjar et al, 2012).…”
Section: Antihypertensive Medications and Cognitionmentioning
confidence: 99%
“…For the neurogenesis signaling pathway, several sources were used. 56, 152155 A list of signaling pathways and proteins used to construct this network is provided in Supplemental Table 1. The selection of pathways and proteins was for illustrative purposes and not intended to be exhaustive.…”
Section: The Evolution Of Food–brain Interactionsmentioning
confidence: 99%